Development of a prototype semi-auto screen-printing machine / Syirin Iffah Iwanjunaedhy - Iwanjunaedhy, Syirin Iffah (2024)
The semi-autonomous screen-printing machine prints any desired screen-printed item on paper or clothing in a semi-automated manner. Another problem that arose in this field of screen printing was the hand production of screen-printed objects, which slowed down the process. This happened because it takes a long time to produce screen-printed goods because human labour is needed. The extrude boss and extrude cut techniques are mostly used in the construction of this machine, and the crank and slider calculation is employed. According to my research of the machine's design in Solid Work, the mechanism's connector will be subjected to a lot of stress, but I took every effort to prevent that from happening so that my prototype could operate as intended. Since the SolidWorks design model is utilised as a guide with the same dimensions to produce the final prototype, there aren't many variations between the SolidWorks prototype design and the final prototype. The real prototype and the design would inevitably differ slightly. For example, the design does not include screws, bolts, nuts, or washers, while the real prototype includes. In conclusion, despite its partial automation, this device facilitates the ink sliding process without requiring human labour, which speeds up the manufacture of screen-printed goods. Finally, I think that this machine will be very beneficial to the screen-printing sector and that someone will eventually increase its capabilities